If it's not what You are looking for type in the equation solver your own equation and let us solve it.
37+y=87y=
We move all terms to the left:
37+y-(87y)=0
We add all the numbers together, and all the variables
-86y+37=0
We move all terms containing y to the left, all other terms to the right
-86y=-37
y=-37/-86
y=37/86
| 8t−4t+3=15 | | 0.6n=0.48 | | 0.75y-0.5y=4000 | | h^2=135 | | 45x-10=14x3 | | 9r-7r+3r=20 | | 56=4(2d+4)* | | x3=64125 | | 350=52t | | w+3w+1=9 | | 4a-4a+a=8 | | -8+9m-4-3m=6* | | x/4+20=-16 | | 17r+15=20r-15 | | 6r+4r=20 | | 3x-8-x=-30 | | x/4+20=-6 | | 16q+2q+2q=20 | | 7v-v+4=10 | | 5x+(-6)=2x+(-3) | | -9-4x-7x=-119 | | 102.3+90+90+x=360 | | 4p^2-2p^2=36 | | y2+4y-y2=16 | | 3s-s+2s-s-s=16 | | 17c-14c=18 | | 9x=13x-8 | | 8j-2j=12 | | 14u+u+2u-14u-u=6 | | X/3-5=2x/5 | | 8x=488 | | 9/4g-12=1/4g-4 |